Fast spin echo imaging of carotid artery dynamics. Issue 4 (13th October 2014) - Boesen, Mari E.; Maior Neto, Luis A. Souto; Pulwicki, Alexandra; Yerly, Jerome; Lebel, R. Marc; Frayne, Richard
<x xml:space="preserve">Abstract</x> Purpose We propose the use of a retrospectively gated cine fast spin echo (FSE) sequence for characterization of carotid artery dynamics. The aim of this study was to compare cine FSE measures of carotid dynamics with measures obtained on prospectively gated FSE images. Methods The common carotid arteries in 10 volunteers were imaged using two temporally resolved sequences: (i) cine FSE and (ii) prospectively gated FSE. Three raters manually traced a common carotid artery area for all cardiac phases on both sequences. Measured areas and systolic–diastolic area changes were calculated and compared. Inter‐ and intra‐rater reliability were assessed for both sequences. Results No significant difference between cine FSE and prospectively gated FSE areas were observed (P = 0.36). Both sequences produced repeatable cross‐sectional area measurements: inter‐rater intraclass correlation coefficient (ICC) = 0.88 on cine FSE images and 0.87 on prospectively gated FSE images. Minimum detectable difference (MDD) in systolic–diastolic area was 4.9 mm2 with cine FSE and 6.4 mm2 with prospectively gated FSE. Conclusion This cine FSE method produced repeatable dynamic carotid artery measurements with less artifact and greater temporal efficiency compared with prospectively gated FSE. Magn Reson Med 74:1103–1109, 2015. © 2014 Wiley Periodicals, Inc.